2002
DOI: 10.17221/3522-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Changes of wheat flour properties during short term storage

Abstract: Two samples of commercial wheat flour from the last year's harvest were stored for three months (in the period from November to April) under different conditions. The ambient temperature and humidity varied during the storage in the dependence on the year season. Certain analytical characteristics (moisture, wet gluten and its extensibility, acidity and falling number) and alveograph behaviour of flour were determined at regular intervals. Flour moisture, acidity, and falling number changed with the time of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 3 publications
9
26
1
3
Order By: Relevance
“…By determining the acidity of the flour, taking the degree of extraction into account, it is possible to monitor the progress of maturing and the possible start of deterioration. Obtained results are consistent with previous studies of flour acidity during storage of wheat and wheat products (Hruškova & Machova 2002). The increase of flour acidity could also be attributed to the increased concentration of free fatty acids and phosphates resulting from increased seed deterioration due to molecular alterations and free radical induced oxidation, as well as to the presence of acid byproducts of advanced Maillard reactions (Rehman & Shah 1999).…”
Section: Resultssupporting
confidence: 90%
“…By determining the acidity of the flour, taking the degree of extraction into account, it is possible to monitor the progress of maturing and the possible start of deterioration. Obtained results are consistent with previous studies of flour acidity during storage of wheat and wheat products (Hruškova & Machova 2002). The increase of flour acidity could also be attributed to the increased concentration of free fatty acids and phosphates resulting from increased seed deterioration due to molecular alterations and free radical induced oxidation, as well as to the presence of acid byproducts of advanced Maillard reactions (Rehman & Shah 1999).…”
Section: Resultssupporting
confidence: 90%
“…These properties are similar to the properties of wheat flour as reported by other researchers [8,9,11]. Statistical analysis shows that packaging types and storage duration has significant effects (p < 0.05) on the moisture content, swelling capacity, water absorption capacity and pH.…”
Section: Resultssupporting
confidence: 88%
“…Wheat flour with low moisture content is more stable during storage. Moisture content can be an indicator of profitability in milling [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flour aging is thought to occur naturally during storage of flour (MirandaGarcia, 2013), was thought to relate to oxidation of flour components including fatty acids and proteins (Cenkowski et al, 2000). Hrušková and Machová (2002) reported that storage time and conditions have an influence on the technological qualities of wheat flour and optimal maturation time depends on both the flour characteristics and storage conditions.…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 561-574mentioning
confidence: 99%